Okra cellulose crystals stabilized Pickering emulsion: A practical tool for soybean oil inclusion to improve nutritive profile of sausages - Nopparat Prabsangob; Sasitorn Hangsalad; Sunsanee Udomrati (Food Chemistry: X)
Pickering emulsions stabilized by okara cellulose crystals and the cellulose crystals modified with tannic acid were prepared and used to substitute porcine fat for sausage preparation. Both used cellulosic materials could effectively preserve dispersibility and heat stability of the emulsions. There was improved sausage stability when the emulsions stabilized by the cellulosic materials were used to replace pork backfat in the sausage formulation. The sausages added with the cellulosic material-based emulsions, especially the ones stabilized by the okara cellulose grafted with tannic acid, possessed better oxidative stability during storage than the control added with porcine fat. Moreover, lowered lipolysis degree could be found for the sausages added with the cellulosic materials stabilized emulsions as compared to the control formulation. Therefore, incorporation of the emulsions stabilized by the cellulosic materials might be a feasible way to improve nutritive profile by lowering saturated fatty acid content and energy uptake of the sausages.